Cratoxylum formosum Extract Protects against Amyloid-Beta Toxicity in a Caenorhabditis elegans Model of Alzheimerʼs Disease - Keowkase, Roongpetch; Weerapreeyakul, Natthida (Planta Medica, 2016)
Amyloid-β, one of the hallmarks of Alzheimerʼs disease, is toxic to neurons and causes cell death in the brain. Oxidative stress is known to play an important role in Alzheimerʼs disease, and there is strong evidence linking oxidative stress to amyloid-β. The herbal plant “Tiew kon” (Cratoxylum formosum ssp. pruniflorum) is an indigenous vegetable that is grown in Southeast Asia. Many reports suggested that the twig extract from C. formosum possesses an antioxidant property. The purpose of this study was to investigate the protective effect of the twig extract from C. formosum against amyloid-β toxicity using the transgenic Caenorhabditis elegans model. This study demonstrated that the extract significantly delayed amyloid-β-induced paralysis in the C. elegans model of Alzheimerʼs disease. Using a genetic approach, we found that DAF-16/FOXO transcription factor, heat shock factor 1, and SKN-1 (Nrf2 in mammals) were required for the extract-mediated delayed paralysis. The extract ameliorated oxidative stress by reducing the level of H2O2, which appeared to account for the protective action of the extract. The extract possesses antioxidant activity against juglone-induced oxidative stress as it was shown to increase survival of the stressed worms. In addition, C. formosum decreased the expression of the heat shock protein-16.2 gene which was induced by thermal stress, indicating its ability to reduce cellular stress. The results from this study support the C. elegans model in the search for disease-modifying agents to treat Alzheimerʼs disease and indicate the potential of the extract from C. formosum ssp. pruniflorum as a source for the development of anti-Alzheimerʼs drugs.
Keywords: Cratoxylum formosum ssp. pruniflorum; Guttiferae; Alzheimerʼs disease; amyloid-β; Caenorhabditis elegans